Effect of diabetes on central macular thickness quantitatively measured using optical coherence tomography at Sidi-Hussein Health Center, Benghazi, Libya - Omear, Mervat; Bukhatwa, Samar; Benkhaial, Fatma (Libyan International Medical University Journal, 2019)
Introduction: Diabetic macular edema (DME) is the most common cause of decreased vision in diabetic retinopathy (DR) and its detection needs equipment and skills. Optical coherence tomography (OCT) is an objective technique that can measure retinal morphologic characteristic which help improving diagnosis and treatment. Aims: This study was conducted to evaluate the role of OCT macula in the screening for DME in patients with diabetes by comparing it to clinical funduscopy in addition to assessing the relationship between central macular thickness (CMT) as measured by OCT macula and the visual acuity of patient. Settings and Design: A retrospective study was done at Sidi Hussein Health center/Benghazi in the period between 2014 and 2017. Subjects and Methods: The data of 393 (786 eyes) patients with diabetes (type II) were reviewed. Cases characteristics records were extracted in addition to fundus examination records (done by noncontact +90-diopter lens). The records of OCT (CMT) were evaluated for agreement with the subjective fundus examination and in relation to other measures. Data were presented as frequencies and the statistical analyses were performed using Statistical Package for the Social Science (Windows version 17.0; SPSS Inc., USA). Results: Around 537 eyes (82%) of eyes with mild DME as diagnosed by OCT were having no DR when examined subjectively. With OCT, it was found that 555 eyes (85%) with mild DME were having good visual acuity (logarithm of the minimum angle of resolution 0.3 and less). About 10 eyes (71%) having severe DME were having duration of diabetes of 10–20 years. Conclusions: OCT is a noninvasive method that can objectively detect and quantify early DME before it affects the vision of patients and it is strongly recommended that this should be the technique of choice for detecting and screening of DME in Libyan patients.
Keywords: Benghazi; central macular thickness; diabetic retinopathy; Libya; optical coherence tomography